Synthesis and Biological Evaluation of Analogue of Delavayin-C: A Cyclic Heptapeptide - V. SHINDE, NIRMALA; HIMAJA, M.; BHOSALE, S.K.; WAGH, R.D. (Asian Journal of Chemistry, 2010)
The synthesis of N-methylated analogue of delavayin-C, a cyclic heptapeptide was carried out by using solution phase technique. The structure of this compound was confirmed on the basis of analytical IR, 1H NMR and FAB MASS spectral data. The elemental analysis of synthesized compound was also carried out. The antibacterial activities of this peptide were carried out against B. subtilis, S. aureus, E. coli and P. aeruginosa. The antifungal activities were carried out against C. albicans and C. neoformans as test organisms. The synthesized compound had shown significant antibacterial as well as antifungal activity.